Way of Improving Learning Effectiveness on Educational Supervision Course in Covid-19 Pandemic: Development of E-Learning-Based Teaching Materials - Andari, Shelly; Hariyati, Nunuk; Mudjito, Mudjito (International Conference on Elementary Education, 2021)
This research is motivated by the need of the availability of teaching materials for students as supporters of online/virtual learning during the Covid-19 pandemic. Availability of E-Learning-based teaching material is expected to overcome the problems faced by students, especially how they understand teaching material on the Educational Supervision Course. This study was designed to produce E-Learning-based teaching materials for Educational Supervision as an effort to improve the effectiveness of learning. Development of teaching materials for Educational Supervision course is using ADDIE Model with the steps to apply this model sequentially include: (1) analyze, (2) design, (3) development, (4) implementation, and (5) evaluation. The result of this study is the implementation of using E-learning method requires instrumental support which includes the device or media used, readiness, and the ability of lecturers to implement a virtual learning system, including teaching material as a single component in the learning system.